2008
DOI: 10.1104/pp.108.117978
|View full text |Cite
|
Sign up to set email alerts
|

Mild Reductions in Mitochondrial Citrate Synthase Activity Result in a Compromised Nitrate Assimilation and Reduced Leaf Pigmentation But Have No Effect on Photosynthetic Performance or Growth  

Abstract: Transgenic tomato (Solanum lycopersicum) plants, expressing a fragment of the mitochondrial citrate synthase gene in the antisense orientation and exhibiting mild reductions in the total cellular activity of this enzyme, displayed essentially no visible phenotypic alteration from the wild type. A more detailed physiological characterization, however, revealed that although these plants were characterized by relatively few changes in photosynthetic parameters they displayed a decreased relative flux through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 65 publications
(66 reference statements)
7
76
0
Order By: Relevance
“…Interestingly, but not surprisingly, as was previously observed in other genotypes deficient in enzymes of the TCA cycle Nunes-Nesi et al, 2005, 2007aSienkiewicz-Porzucek et al, 2008), the activities of other key enzymes of carbon metabolism were largely unaltered, as were the levels of phosphorylated intermediates, suggesting that the increased CO 2 assimilation rates were not mediated by a classical metabolic mechanism. Indeed, despite the fact that the previously characterized lines displayed large alterations in the expression of photosynthesis-related genes (Urbanczyk-Wochniak et al, 2006), the SDH lines described here were characterized by very few transcriptional changes.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Interestingly, but not surprisingly, as was previously observed in other genotypes deficient in enzymes of the TCA cycle Nunes-Nesi et al, 2005, 2007aSienkiewicz-Porzucek et al, 2008), the activities of other key enzymes of carbon metabolism were largely unaltered, as were the levels of phosphorylated intermediates, suggesting that the increased CO 2 assimilation rates were not mediated by a classical metabolic mechanism. Indeed, despite the fact that the previously characterized lines displayed large alterations in the expression of photosynthesis-related genes (Urbanczyk-Wochniak et al, 2006), the SDH lines described here were characterized by very few transcriptional changes.…”
Section: Discussionmentioning
confidence: 49%
“…With the exception of a handful of studies concerning root metabolism (Koyama et al, 2000;Ló pez-Bucio et al, 2000, 2003van der Merwe et al, 2009), the majority of studies have focused on leaf tissue, despite the fact that the role of the TCA cycle in the illuminated leaf remains somewhat contentious (Tcherkez et al, 2005;Nunes-Nesi et al, 2007a). Intriguingly, quite diverse effects were observed upon downregulation of the various steps of the cycle, with deficiency of expression of aconitase and the mitochondrial malate dehydrogenase resulting in enhanced photosynthetic rates Nunes-Nesi et al, 2005), whereas inhibition of either citrate synthase, succinyl CoA ligase, or isocitrate dehydrogenase had little effect on the rates of photosynthesis itself and relatively minor consequences on photosynthetic metabolism in general (Studart-Guimarã es et al, 2007;Sienkiewicz-Porzucek et al, 2008Sulpice et al, 2010). By contrast, downregulation of the expression of fumarase restricted photosynthesis and plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tomato (Solanum lycopersicum) plants with reduced expression of aconitase or malate dehydrogenase showed an enhanced photosynthetic performance (Carrari et al, 2003;NunesNesi et al, 2005). In contrast, tomato plants with less succinyl-CoA ligase or citrate synthase, or Arabidopsis plants with less mitochondrial isocitrate dehydrogenase, have no change in photosynthesis (Lemaitre et al, 2007;Studart-Guimarães et al, 2007;Sienkiewicz-Porzucek et al, 2008), while tomato plants with less fumarase showed a decrease in photosynthesis . The reasons for these intriguing, quite diverse effects remain somewhat unclear at a mechanistic level.…”
mentioning
confidence: 83%
“…Other mutants also show an accumulation in glycine that is not directly linked to photorespiration. T-DNA bou-2 mutants in Arabidopsis and those with antisense targeting of TCA cycle enzymes in tomato (Solanum lycopersicum) accumulate glycine, showing a close relationship between respiration and photorespiration (Carrari et al, 2003;Sienkiewicz-Porzucek et al, 2008;Eisenhut et al, 2013b). Unexpectedly, 2PG-phosphatase (pglp1) T-DNA lines also demonstrate an increase in glycine levels even though PGLP acts before glycine formation (Timm et al, 2012).…”
Section: Discussionmentioning
confidence: 99%